The Answers community requires more information for this question. Please edit your question to include more context.
Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. It is not clear whether what needs to be solved is an equation or an inequality.
Also, this browser does not support graphics.
5+y+2y? = 5+3y?
x+3y=2 x= -5 y = 1
5*3y+1+12y-1 = 15y+1+12y-1 = 27y.
x = 5, y = -1
x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5
3y + 8 = 3 -8 -8 3y=-5 (3y)/3=-5/3 y=(-5/3)
5+y+2y? = 5+3y?
10y= 6y+5+3y 10y=6+9y y=6
x+3y=2 x= -5 y = 1
5*3y+1+12y-1 = 15y+1+12y-1 = 27y.
3y + 2y + 4 + 1 = 805y + 5 = 805y = 75y = 15
If you mean: 80 = 3y+2y+4+1 then 80 =5y+5 and so y = 15
I don't know whether it's y^2-3y+2+3y-4y-5 or 2y-3y+2+3y-4y-5, so I'll do both.y^2-3y+2+3y-4y-5y^2+(-3y+3y-4y)+(2-5); group them togethery^2+(-4y)+(-3)y2-4y-3OR2y-3y+2+3y-4y-5(2y-3y+3y-4y)+(2-5); group them together(-2y)+(-3)-2y-3
x = 5, y = -1
3y - 3 = 2y + 5 3y - 2y = 5 + 3 y = 8
x + y = -2 2x + 3y = -9 You solve this by elimination - multiply both sides of first equation by 3, then subtract, solve for x, then substitute in any of the equations to solve for y 3x + 3y = -6 2x + 3y = -9 subtracting, x = 3 substituting into 1st equation, y = -2-3 = -5
2x-11